Government Employees with Work Agreements in the Politics of Law of the Formation of the State Civil Apparatus Law - Miftahul Jannah; Lia Riesta Dewi; Muhammad Donny Adhie Pratista; I Made Andhika Darma Perkasa (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2026)
This study analyzes the legal politics underlying the position of Government Employees with Work Agreements (PPPK) following the enactment of Law Number 20 of 2023 on the State Civil Apparatus (ASN). This legislative reform marks a fundamental shift in Indonesia’s public personnel policy—from a rigid bureaucratic paradigm toward a more inclusive and justice-oriented merit system. The research employs a normative juridical method with statutory and conceptual approaches, using a comparative analysis between the 2014 ASN Law and the 2023 ASN Law. The findings indicate that the 2023 ASN Law introduces a significant reorientation of PPPK’s legal status through equal rights, stronger legal protection, and enhanced social security guarantees. Nevertheless, several legal challenges remain, particularly regarding pension schemes, employment contracts, and non-discrimination in managerial positions. The legal politics of the 2023 ASN Law reflect the state’s commitment to building a professional, accountable, and adaptive bureaucracy, although its success largely depends on the consistent implementation of justice, legal certainty, and utility principles in the national civil service management system.